Echocardiographyc changes in kidney transplanted patients - Mirta C. Flores Cubías; Humberto L. Ramos González; Gilberto Cairo Sáez (ECIMED, 2014)
Introduction: Cardiovascular affectation is frequent in the patients with chronic kidney failure and cardiovascular complications constitute the first cause of death in these patients. Objective: identify echocardiographic changes in transplanted renal patients in the Hospital "Arnaldo Milián" of Santa Clara.Methods: A descriptive - prospective study was carried. 46 patients were studied, The average age was 45,2 years, an echocardiogram was perform before transplant and at three, six and nine months after it. Conclusions: Six patients died during the study. In pre-transplant patients the average ejection fraction was 53,4%, and the main findings were left ventricular hypertrophy and pericardial effusion, present in 73,9% of patients. The longer the time on hemodialysis, the greater the deterioration of the cardiac function. After kidney transplant pericardial effusion as well as the cardiac function improved significantly.